(3JMUjdGJ HgejfGRs - (3HgefjGQ Hf GdeQRHGf GdGPQHjLGf, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEfi eMUd ai gPg GdQSGdI ddNGd GdQFjS GdCLd CHj efUhQ HgQGe Hf NQTjO GdJi gPHgG GdTjN GdQFjS CHh Ydi GdMSjf Hf YHO Gddg hjfbSe gPG GdcJGH Edi KdGKI cJH aGdcJGH GdChd ai GdefWb s
(3BNQgG (B:s
(3aEPG GdSWM hGdNW jhLOGf bHd GdfbWI adGJchf GdfbWI Ydg dhLhO GdNW hbO cfG HjfG Cf gPg GdMOhO eJCNQI ai GdhLhO Yf GdLSe Je GdLR AGdChd ef cJGH GdJMUjd s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJjcGf s
Keywords: (3GdadSaI hGdefWbs